EVALUATION OF ANTIBACTERIAL ACTIVITY OF Amaranthus spinosus EXTRACT AGAINST Streptococcus mutans: AN IN-VITRO STUDY - Nisa, Fakhrun; Warella, Juen Carla; Hursepuny, Valentine; Bension, Johan Bruyif; Rahma, Khairunnida (Folia Medica Indonesiana, 2025)
Streptococcus mutans is a component of the normal oral flora that can become a primary pathogen, leading to dental caries and tooth decay. Tooth decay and dental caries are the most common oral health issues worldwide. Treatment of dental caries and tooth decay represents a crucial effort in addressing global health concerns. One alternative treatment the community used to treat dental caries and tooth decay is thorn spinach (Amaranthus spinosus). Thorn spinach leaves contain bioactive compounds with potential antibacterial properties, including flavonoids, tannins, saponins, and alkaloids. This study aimed to evaluate the antibacterial activity of thorn spinach leaf extract at concentrations of 10%, 20%, 40%, 80%, and 100% against S. mutans. This study employed a descriptive observational design, utilizing a laboratory-based experimental approach. The leaves were extracted using the maceration technique, employing methanol and ethyl acetate as the solvents. The results showed that these extracts can inhibit the growth of S. mutans. The inhibition zones were observed for the methanol extract at concentrations of 10% (6.84 ± 5.36), 20% (12.95 ± 0.85), 40% (8.45 ± 1.00), 80% (14.66 ± 4.17), and 100% (4.74 ± 2.88). For the ethyl acetate extract, the mean inhibition zones were at concentrations of 10% (0.08 ± 0.15), 20% (8.71 ± 4.04), 40% (11.99 ± 2.44), 80% (14.79 ± 5.13), and 100% (15.00 ± 3.09). These findings indicated that, among the two types of solvents utilized, ethyl acetate was more effective than methanol, demonstrating the highest inhibitory activity with moderate to strong inhibitory categories.